Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems 2019
DOI: 10.1145/3290605.3300478
|View full text |Cite
|
Sign up to set email alerts
|

Pay Attention, Please

Abstract: Participant engagement in online studies is key to collecting reliable data, yet achieving it remains an often discussed challenge in the research community. One factor that might impact engagement is the formality of language used to communicate with participants throughout the study. Prior work has found that language formality can convey social cues and power hierarchies, affecting people's responses and actions. We explore how formality influences engagement, measured by attention, dropout, time spent on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…They found that the ethnic variety lead to stronger agreeability than the formal variety, and the informal and ethnic variations gave rise to higher relatedness with the speaker. At the perception level, language formality has also been shown to improve participants' attention during online experiments (August & Reinecke 2019). In another exploratory sociophonetic study, Winter & Grawunder (2012) show that language formality modulates a number of vocal expressions in Korean.…”
Section: Language Register (Formal Vs Colloquial)mentioning
confidence: 96%
“…They found that the ethnic variety lead to stronger agreeability than the formal variety, and the informal and ethnic variations gave rise to higher relatedness with the speaker. At the perception level, language formality has also been shown to improve participants' attention during online experiments (August & Reinecke 2019). In another exploratory sociophonetic study, Winter & Grawunder (2012) show that language formality modulates a number of vocal expressions in Korean.…”
Section: Language Register (Formal Vs Colloquial)mentioning
confidence: 96%
“…Table 3 lists demographics and topic familiarity. Extrinsic motivations like payment can lead participants to maximize pay at the expense of data quality (e.g., by rushing through a study [9,106]). Studies 1 and 3 used Master Turkers, who have been shown to provide data quality equivalent to intrinsically motivated participants (e.g., participants motivated by supporting science) [106].…”
Section: 14mentioning
confidence: 99%
“…Adapting interfaces to different users has the potential to improve usability [13,87], aesthetic judgements [28,69], and trust [61,68]. Increasingly, language styles, such as community language norms [26], formality [9], and text complexity [11,95] have been the focus of adaptable user interfaces. Work has shown that language styles can impact behavior in online experiments [9], counseling conversations [4], online communities [26], and security interfaces [98].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nguyen et al showed that framing a task with positive affective language may reduce the frustration of participants and lead to an increase in work quality [48]. The framing of a task may also influence the attention of a worker [9]. Morris et al applied affective priming theory in crowdsourcing [46].…”
Section: Computational Priming In Crowdsourcing Tasksmentioning
confidence: 99%